THE PROBLEMS ON ESTIMATION OF THE RATE OF SUSTAINABILITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
Launching of the sustainable development means solving quantitative problems of controlling of the state of global circulations, functioning of climate machine etc. The main processes determining sustainability of the state of the natural environment area) carbon cycle and the work of the climate machine which in fact are closely connected,b) water cycle, (over)use and pollution of global and regional water resources,c) also the change of the flow of organic substance and biogenic elements into one-way flow “land-»town” instead of the natural circulation “soil-»plant-»animal (human)— »soil”.